Single Cell Analysis Reveals Concomitant Transcription of Pluripotent and Lineage Markers During the Early Steps of Differentiation of Embryonic Stem Cells - Lanctôt, Christian (Stem cells (Dayton, Ohio), 2015)
The differentiation of embryonic stem cells is associated with extensive changes in gene expression. It is not yet clear whether these changes are the result of binary switch-like mechanisms or that of continuous and progressive variation. Here, I have used immunostaining and single molecule RNA fluorescence in situ hybridization (FISH) to assess changes in the expression of the well-known pluripotency-associated gene Pou5f1 (also known as Oct4) and early differentiation markers Sox1 and T-brachyury in single cells during the early steps of differentiation of mouse embryonic stem cells. I found extensive overlap between the expression of Pou5f1/Sox1 or Pou5f1/T-brachyury shortly after the initiation of differentiation towards either the neuronal or the mesendodermal lineage, but no evidence of correlation between their respective expression levels. Quantitative analysis of transcriptional output at the sites of nascent transcription revealed that Pou5f1 and Sox1 were transcribed in pulses and that embryonic stem cell differentiation was accompanied by changes in pulsing frequencies. The progressive induction of Sox1 was further associated with an increase in the average size of individual transcriptional bursts. Surprisingly, single cells that actively and simultaneously transcribe both the pluripotency- and the lineage-associated genes could easily be found in the differentiating population. The results presented here show for the first time that lineage priming can occur in cells that are actively transcribing a pluripotent marker. Furthermore, they suggest that this process is associated with changes in transcriptional dynamics.
Keywords: Brachyury Protein; protein brachyurie; SOXB1 Transcription Factors; Cell Differentiation; hybridizace in situ fluorescenční; fetální proteiny; vývojová regulace genové exprese; pluripotentní kmenové buňky; Octamer Transcription Factor-3; Embryonic stem cells; Single-Cell Analysis; Mice; Embryonic Stem Cells; In Situ Hybridization, Fluorescence; Cell Lineage; embryonální kmenové buňky; Gene Expression Regulation, Developmental; Early differentiation; buněčný rodokmen; zvířata; proteiny T-boxu; T-Box Domain Proteins; oktamerní transkripční faktor 3; Pluripotent Stem Cells; Single molecule RNA fluorescence in situ hybridization; transkripční faktory SOXB1; Lineage priming; myši; analýza jednotlivých buněk; Transcriptional dynamics; buněčná diferenciace; Fetal Proteins; Animals